Fertile Links? Connections between tourism activities, socioeconomic contexts and local development in European rural areas - Raschi, Antonio; Melo Figueiredo, Elisabete Maria (Strumenti per la didattica e la ricerca, 2013)
In many European regions, rural areas are facing major challenges in economic and social terms, consequence of transformations in the role and meaning of agriculture. The loss of the productive character strongly contributed to the emergence of new roles and functions, particularly related to leisure and tourism. The book aims to discuss questions directly related to the connections between rural tourism and local socioeconomic contexts, presenting diverse theoretical and methodological perspectives and diff erent case studies from various European regions. The book addresses the relationships among rural tourism and the complex interactions, confl icts and innovative processes developing in rural territories as consequence of the implementation of tourism activities. The book responds to some relevant and not yet comprehensively researched aspects within this topic, especially in what extent tourism, in its various forms and processes, might give an important contribution to rural development.